2000
DOI: 10.1055/s-2000-9458
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphopeptide Corresponding to the Cytosolic Stretch Connecting Transmembrane Segments 8 and 9 of the Plasma Membrane H+‐ATPase Binds 14‐3‐3 Proteins and Inhibits Fusicoccin‐Induced Activation of the H+‐ATPase

Abstract: A putative consensus domain for binding of 14‐3‐3 proteins to the plasma membrane (PM) H+‐ATPase was identified in the highly‐conserved sequence RSR(p)SWSF [where (p)S is Ser776 of the maize isoform MHA2], localized in the cytosolic stretch connecting transmembrane segments 8 and 9. A 15 amino acid biotinylated phosphopeptide comprising this motif: i) bound a recombinant 14‐3‐3 protein, ii) inhibited fusicoccin‐induced stimulation of the PM H+‐ATPase activity both in PM isolated from germinating radish (Raphan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…With regard to this it should be noted that the loss of the penultimate amino acid of H ϩ -ATPase, the phosphothreonine, is sufficient to lose the 14-3-3 binding to the regulatory domain (30,31). In addition, it would be interesting to define the biological significance of the finding of an interaction of 14-3-3 proteins with H ϩ -ATPase at a site other than its C-terminal domain (32). Like in animals (1) in plants too the 14-3-3 proteins act as multifunctional regulatory proteins, in the regulation of the metabolism, of the transcription and of the organellar protein trafficking (2,33).…”
Section: Discussionmentioning
confidence: 97%
“…With regard to this it should be noted that the loss of the penultimate amino acid of H ϩ -ATPase, the phosphothreonine, is sufficient to lose the 14-3-3 binding to the regulatory domain (30,31). In addition, it would be interesting to define the biological significance of the finding of an interaction of 14-3-3 proteins with H ϩ -ATPase at a site other than its C-terminal domain (32). Like in animals (1) in plants too the 14-3-3 proteins act as multifunctional regulatory proteins, in the regulation of the metabolism, of the transcription and of the organellar protein trafficking (2,33).…”
Section: Discussionmentioning
confidence: 97%
“…However, 14-3-3 proteins also bind to the H ϩ -ATPase independently of FC (Fullone et al, 1998), and this FC-independent binding is phosphorylation dependent and occurs in a truncated H ϩ -ATPase lacking the C-terminal domain (Jahn et al, 1998). Recently, Marra et al (2000) identified a sequence of the PM H ϩ -ATPase highly conserved in different isoforms of different plants and localized in the cytosolic stretch connecting transmembrane segments 8 and 9, which mimics the known 14-3-3 binding motif (Muslin et al, 1996;Yaffe et al, 1997). A phosphopeptide corresponding to such a sequence bound a 14-3-3 protein and inhibited FC binding and FCinduced activation of the PM H ϩ -ATPase; all of these effects were dependent on the phosphorylation of a Ser residue.…”
Section: Discussionmentioning
confidence: 99%
“…When provided in large excess, it presumably titrates the endogenous 14-3-3 (see the use of this peptide in Refs. 15,20,39). The injection of this peptide strongly decreased the level of I KAT1 in oocytes (70% Ϯ 6 at Ϫ150 mV, n ϭ 4); in control experiments (data not shown) heat-inactivated Raf 621p decreased the current at Ϫ150 mV of 38% Ϯ 4 (n ϭ 4).…”
Section: Recombinant 14-3-3 Proteins Increase the Activity Of Kat1 Chmentioning
confidence: 99%